Heterogeneous and Flexible Transmission of mcr-1 in Hospital-Associated Escherichia coli - Yingbo Shen; Zuowei Wu; Yang Wang; Rong Zhang; Hong-Wei Zhou; Shaolin Wang; Lei Lei; Mei Li; Jiachang Cai; Jonathan Tyrrell; Guo-Bao Tian; Congming Wu; et al. (mBio, 2018)
ABSTRACT The recent emergence of a transferable colistin resistance mechanism, MCR-1, has gained global attention because of its threat to clinical treatment of infections caused by multidrug-resistant Gram-negative bacteria. However, the possible transmission route of mcr-1 among Enterobacteriaceae species in clinical settings is largely unknown. Here, we present a comprehensive genomic analysis of Escherichia coli isolates collected in a hospital in Hangzhou, China. We found that mcr-1-carrying isolates from clinical infections and feces of inpatients and healthy volunteers were genetically diverse and were not closely related phylogenetically, suggesting that clonal expansion is not involved in the spread of mcr-1. The mcr-1 gene was found on either chromosomes or plasmids, but in most of the E. coli isolates, mcr-1 was carried on plasmids. The genetic context of the plasmids showed considerable diversity as evidenced by the different functional insertion sequence (IS) elements, toxin-antitoxin (TA) systems, heavy metal resistance determinants, and Rep proteins of broad-host-range plasmids. Additionally, the genomic analysis revealed nosocomial transmission of mcr-1 and the coexistence of mcr-1 with other genes encoding β-lactamases and fluoroquinolone resistance in the E. coli isolates. These findings indicate that mcr-1 is heterogeneously disseminated in both commensal and pathogenic strains of E. coli, suggest the high flexibility of this gene in its association with diverse genetic backgrounds of the hosts, and provide new insights into the genome epidemiology of mcr-1 among hospital-associated E. coli strains. IMPORTANCE Colistin represents one of the very few available drugs for treating infections caused by extensively multidrug-resistant Gram-negative bacteria. The recently emergent mcr-1 colistin resistance gene threatens the clinical utility of colistin and has gained global attention. How mcr-1 spreads in hospital settings remains unknown and was investigated by whole-genome sequencing of mcr-1-carrying Escherichia coli in this study. The findings revealed extraordinary flexibility of mcr-1 in its spread among genetically diverse E. coli hosts and plasmids, nosocomial transmission of mcr-1-carrying E. coli, and the continuous emergence of novel Inc types of plasmids carrying mcr-1 and new mcr-1 variants. Additionally, mcr-1 was found to be frequently associated with other genes encoding β-lactams and fluoroquinolone resistance. These findings provide important information on the transmission and epidemiology of mcr-1 and are of significant public health importance as the information is expected to facilitate the control of this significant antibiotic resistance threat.